Cost Reducing Inputs, Underproduction and Economic Welfare - Gianluca Fiorentini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
The object of this paper is to investigate social and strategic overinvestment in cost reducing inputs, when such investment enters directly in the other firms' objective function.
Keywords: 330